Snapshot : Sponsors from Singapore and Infrastructure Projects with Private Participation (1990-2011) - Militaru, Andreea (World Bank, Washington, DC, 2014)
A total of United States (U.S.) 38 billion dollars in investment commitments, 107 infrastructure projects, 19 countries, and 4 sectors: this is a quick snapshot of what Singaporean companies invested in private infrastructure projects from 1990 to 2011.1 Nearly 67 percent of total investment and over 85 percent of all infrastructure projects were implemented after 2000. Private investment peaked in 2007 when Singaporean sponsors invested over U.S. 6.4 billion dollars and developed a number of 19 new infrastructure projects. The project was expected to cost U.S. 1,426.38 million dollars and achieved financial closure in September 2007. A consortium of banks with rural electrification corporation in the lead provided the debt for the project.